A01 Natural History Of HD In Humans. (17th September 2014) - Tabrizi, SJ
Abstract : Understanding of HD pathogenesis is evolving, and there are a number of candidate therapeutics with potential disease-modifying effects that are currently being tested. With potential disease-modifying therapies in development, there is a drive to improve clinical trial design, optimise study cohorts, and identify potential trial outcome measures that are sensitive to disease-related change. Since 2008 TRACK-HD has chronicled the earliest stages of the neurodegenerative disease processes in premanifest and mild to moderately symptomatic individuals who carry the HD expansion mutation. Annual assessments included a battery of potential clinical and biological outcome measures with the aim of understanding the preclinical and early phases of neurodegeneration, phenotypic correlates of neuronal dysfunction, and of establishing sensitive and specific clinical and biological markers of disease progression. Published TRACK-HD data includes longitudinal effect sizes for disease-progression in early stage HD over 24 months and detailed phenotypic dissection of disease progression in both premanifest and early-HD over 36-months, identifying predictors of clinical decline that are independent of age and CAG effects. Both have important implications for clinical trial design, and further our understanding of disease progression across the spectrum of HD. We are now in a position to model progression in a range of functional and imaging measures across the spectrum of HD, and our ongoing research aims to identify neural compensatory networks that may occur in the premanifest phase of neurodegeneration in HD. I will present new unpublished data from TRACK-HD, mapping basal ganglia connectivity and degeneration of cortico-striatal connectivity with disease progression. I will also present new data from the Track-On HD study in which the aim was to dissect the relationship between brain structure, function and behaviour and identify whether normal performance in those with higher disease load indicates compensatory brain activity in pre-symptomatic stages of the disease. To this end the interactive effect of structural degeneration on cognitive behaviour, sensorimotor networks, fMRI activity and resting state connectivity have been explored and its relevance to the natural history of HD will be presented.